Comparison of efficacy and adverse effects of CD19/20 CART versus CD19 single-target CART in R/R DLBCL: a single-center retrospective study - Xue, Bin; Liu, Yifan; Li, Bing; Lu, Yan; Zhou, Lili; Ye, Shiguang; Lu, Huina; Luo, Xiu; Liang, Aibin; Li, Ping (Frontiers in Immunology, 2025)
PurposeCD19 Chimeric Antigen Receptor T-cell therapy (CART) represents a groundbreaking approach in the treatment of relapsed or refractory diffuse large B-cell lymphoma (R/R DLBCL). However, a subset of patients fails to achieve optimal outcomes with CD19-targeted CAR T-cells alone. To address these limitations, the development of multi-targeted CART therapies has become a focal point of innovative research. This study aims to compare the therapeutic efficacy and adverse events of dual-target versus single-target CART therapies in R/R DLBCL patients through a single-center retrospective analysis.MethodsWe included 70 patients with R/R DLBCL treated at Shanghai Tongji Hospital between January 1, 2019, and December 31, 2021. Among them, 20 patients received dual-target (CD19/20) CART, while 50 underwent CD19 CART.ResultsThe CD19/20 CART group demonstrated significantly superior three-month efficacy to the CD19 CAR T-cell group, with a notably higher complete response (CR) rate. The median progression-free survival (PFS) and overall survival (OS) were 28.6 and 31.8 months longer in the Bi-CART group compared to the CD19 CAR T-cell group. However, the two groups had no significant differences in overall PFS, duration of response (DOR), or OS. The CD19/20 CART group exhibited a higher incidence of cytokine release syndrome (CRS), hematological toxicity, infections, and secondary primary tumors.ConclusionThis study highlights the superior efficacy of dual-target CAR T-cell therapy in managing R/R DLBCL patients. The dual-target therapy significantly extended median survival compared to CD19 single-target CAR T-cell therapy. However, the enhanced therapeutic benefits were accompanied by a higher incidence of adverse effects.